Implementasi Virtual Private Network Menggunakan L2TP/IPsec pada BBPK Jakarta - Sumarna Sumarna; Aditya Maulana (Universitas Bandar Lampung (UBL), 2021)
Some companies already use computer networks as a tool to communicate, including companies that already have subsidiaries in various regions. This is inseparable from the use of an internet network that can be interconnected. In BBPK Jakarta network, data delivery and exchange conducted between Cilandak building employees and Hang Jebat building still use email and WhatsApp facilities. In addition to being less secure or having the possibility of being hacked by irresponsible parties, it is also constrained by the capacity limit of files to be sent in one delivery. VPN network is one of the facilities in microtic hardware that allows to create a network within an internet network. VPN network with L2TP/IPsec tunnel is expected to help communication, employee activities at head office and branch offices, increase shipping security and reduce the possibility of threats that can occur when sending data in the network.